No association between head injury with loss of consciousness and Alzheimer disease pathology—Findings from the University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age. (10th May 2019) - Robinson, Andrew C.; Davidson, Yvonne S.; Horan, Michael A.; Cairns, Maggie; Pendleton, Neil; Mann, David M.A.
Abstract : Objectives: Head injury with loss of consciousness (HI‐LOC) is a common occurrence. Some studies have linked such injuries with an increased risk of Alzheimer disease (AD). However, recent large clinicopathologic studies have failed to find a clear relationship between HI‐LOC and the pathological changes associated with AD. The present study aims to further investigate the relationship between HI‐LOC and AD pathology in the elderly. Methods/Design: History of HI‐LOC in participants in the University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age was ascertained. The donated brains of 110 of these individuals were assessed for AD pathology using consensus guidelines. Analyses aimed to elucidate relationships between HI‐LOC and AD pathology. Results: No associations were found between incidence of HI‐LOC and regional AD pathology or any of the three established measures of the neuropathology associated with AD: CERAD score, Thal phase, or Braak stage. Conclusions: Single incidences of HI‐LOC may not be sufficient to cause the pathology associated with late‐stage AD. Other routes of damage, such as diffuse axonal injury or Lewy body pathology, may play a greater role in causing cognitive impairment associated with head injury.